Egg banks of ostracods (Crustacea) in temporary lakes of a tropical floodplain. - Rosa, Jonathan da (2019)
Aquatic environments often undergo stochastic drought events, which force communities to use survival adaptive strategies. During prolonged drought periods, some aquatic organisms produce drought-resistant eggs in response to these conditions, to persist in the environment. The main aim of this study was to evaluate the egg banks of ostracods in temporary lakes in the Upper Paraná River floodplain, Brazil, analyze the contribution to diversity and spatial variation. Sediment samples were collected during the dry season in these temporary lakes, and sediments were oven-dried, then re-hydrated and kept in germinating chambers, with controlled temperature and photoperiod. Two distinct approaches were used. The first approach compared the passive (egg bank) and active communities of ostracods in a temporary lake (Osmar Lake). The richness and abundance of ostracods were higher in the passive community, and species composition differed between passive and active communities. This is associated with series of different drought/inundation cycles and the accumulation of the resting eggs from different generations. The passive community added species not found in the active community, thus contributing to the maintenance and enrichment of the local and regional fauna. Flooding events probably also contributed to the entrance of allochthonous ostracod species in the Osmar Lake by pleuston of floating macrophytes. The second approach evaluated the spatial variation of ostracod resting eggs between the edge and the centre of five temporary lakes. The results showed that the abundance and species composition are homogeneous between different regions (edge and centre) of the lakes. Flood events may be responsible for the homogenization of the egg banks, owing to the connection of lakes with the principal channel of the Paraná River. During flooding, water masses powerfully enter the temporary lakes and can redistribute the sediments. Thirteen ostracod species hatched from resting eggs (or torpidity stages). These species are resilient to extreme events and have invasive potential, owing to a combination of asexual reproduction (parthenogenesis) and of passive dispersal by drought resistant eggs. The resting eggs contributed to the species diversity and structure of the ostracod community in these temporary lakes. Thus, these environments represent a relevant regional pool of species for tropical floodplain environments.